Development of lens-free holographic microscopes using multiheight and multispectral phase recovery methods - D\'Almeida, Camila de Paula (2023)
Since its invention in century XVI, microscopy is one of the most important optics techniques. Its use has revolutionized many knowledge areas and these applications have driven improvements in the technique itself. The lens-free microscope has emerged as an alternative to traditional optical microscopes. This recent technique has the advantage to decouple the imaging resolution from the field of view and also to provide very compact and low-cost systems. Lens-free microscopes based on hologram acquisition produce amplitude and phase images of the same observed scene, using a digital imaging process to perform phase recovery. This study aims to develop and test portable and automated lens-free holographic microscopes, based on open-source software, using two methods for imaging acquisition and processing: multiheight and multispectral. The first applied method is the multiheight, which records a sequence of holograms with different sensor-sample distances and uses them as input data to recover phase values of the light that better describes the recorded scene. Multispectral method was also used to record holograms using light with emission at different spectral ranges and composes amplitude and phase images from this imaging information. Homemade open-source algorithms were developed in Python language to control the component device and to perform the digital imaging processing. Both lens-free microscopes were tested using standard test targets to define the spatial resolution of each one. Besides, it has been applied to imaging different types of biological samples to analyze their amplitude and phase images in different conditions. Thus, these systems were used to image different cells and microorganisms. More robust analyses were performed to provide yeast and Giardia cyst counting. Therefore, two portable, low-cost, automated, and based on open-source software lens-free holographic microscopes were developed and tested in this study, using multiheight and multispectral methods to perform amplitude and phase images with almost 30mm2 and about 5μm of resolution. Both systems proved to be efficient for observing cells and microorganisms without the need for labels.